2017
DOI: 10.1089/lap.2016.0392
|View full text |Cite
|
Sign up to set email alerts
|

Large Sized Left Inferior Phrenic Artery and Parahiatal Type of Diaphragmatic Hernia Generating Confusion During Robotic Surgical Repair

Abstract: The challenge of the repair of this rare, parahiatal type of diaphragmatic hernia where a large sized left inferior phrenic artery was also encountered was successfully mitigated by the use of the intraoperative Doppler ultrasound and by compliance with the basic steps of the procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…The search identified 16 relevant articles published in the language of English. [1][2][3][4][5][8][9][10][11][12][13][14][15][16][17] Together with two cases from our clinical work, a total of 27 parahiatal hernia patients were included in the present study; 15 cases were female, 12 cases were male, the average age was 51.8 years old (range: 4-80 years old). The overview and summarized data are presented in Tables 1 and 2, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The search identified 16 relevant articles published in the language of English. [1][2][3][4][5][8][9][10][11][12][13][14][15][16][17] Together with two cases from our clinical work, a total of 27 parahiatal hernia patients were included in the present study; 15 cases were female, 12 cases were male, the average age was 51.8 years old (range: 4-80 years old). The overview and summarized data are presented in Tables 1 and 2, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, mesh was used in 14 cases (Tables 1,2). The reasons of using mesh for parahiatal repair were following: hernia defect was closed under tension, the diaphragm was thinned out and may subsequently tear, the closure was tension free, but a tendency of the hiatus enlargement was noticed 0014. The mesh should be cut and fixed to the hiatus area snugly, as described by various authors for large hiatal hernia repairs 0023.…”
Section: Discussionmentioning
confidence: 99%
“…Robotic surgery developed in the last decades and it has been successful applied to repairs of these type of hernias. Our review of literature showed that only 11 cases of trans-abdominal robotic repairs of congenital Morgagni-Larrey diaphragmatic hernias in adults have been described [5] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [22] . None of these cases required conversion to open surgery and post-operative course was free of major complications; robotic repair, even in comparison with laparoscopic techniques, appears to be associated with a shorter length of stay [7] , [13] .…”
Section: Discussionmentioning
confidence: 99%
“…Using “parahiatal” and “hernia” as search terms, we searched PubMed literature from 1968 to 2021, and we identified 20 cases of parahiatal hernia after the exclusion of irrelevant and secondary cases [1] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] . Of these 20 cases, 9 were primary parahiatal hernia complicated by a sliding hiatal hernia ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%